A multilocus perspective on the phylogenetic relationships and diversification of rodents of the tribe Abrotrichini (Cricetidae: Sigmodontinae). (31st July 2014) - Cañón, Carola; Mir, Daiana; Pardiñas, Ulyses F. J.; Lessa, Enrique P.; D'Elía, Guillermo
<x xml:space="preserve">Abstract</x> Abrotrichini is a recently defined and diagnosed tribe of Sigmodontinae with a complex taxonomy. Abrotrichine genera, Abrothrix (including Chroeomys), Chelemys, Geoxus, Notiomys and Pearsonomys, are mostly distributed in the central and southern Andes and adjacent lowlands and show terrestrial and fossorial habits. Recent studies have evidenced some incongruence between current taxonomy and abrotrichine phylogeny, such as the polyphyly of Chelemys and paraphyly of Geoxus respect to Pearsonomys. We used DNA sequence data of six loci (one mitochondrial and five nuclear) to resolve the relationships within the tribe. Independent and combined analyses of these loci were carried out using parsimony, maximum likelihood and Bayesian inference. Estimates of divergence time of the main lineages of abrotrichines were calculated with a molecular clock using as calibration, a fossil recently found. The concatenated data set increased the resolution and defined the relationships within the tribe. Our phylogenetic analyses corroborate that Abrothrix is sister of a clade containing the long‐clawed abrotrichines. We recovered two main clades within Abrothrix that match morphologic variation and geographic distribution of its species. In addition, we corroborated the lack of monophyly of Chelemys and the lack of monophyly of Geoxus. We discuss different taxonomic scenarios to abrotrichine classification reflects the phylogenetic relationships obtained in this study. Our molecular clock estimated the Abrotrichini crown age to be around the early Pliocene (4.4 Ma) and suggest that the tribe diversified over a short period of time.